Electrochemical Degradation Caused by Mechanical Damage in Silicon Negative Electrodes. (6th January 2017) - Yoshida, Naoki; Sakamoto, Tadashi; Kuwata, Naoaki; Kawamura, Junichi; Sato, Kazuhisa; Hashida, Toshiyuki
Abstract : Silicon is a promising anode material for lithium ion batteries application due to its high electrochemical capacity. Unfortunately, silicon undergoes a volume expansion of 300 400% under the full lithiation condition and suffers from severe capacity fade, which limits its successful application in commercial cells. In this study, we used in situ acoustic emission method for detecting mechanical damage in the silicon electrode. The present study revealed the mechanism of degradation in a silicon electrode of the lithium ion batteries. It was shown that the long-term performance of silicon electrode was dictated by its spallation during the discharge processes. This study demonstrated that the AE method developed was a powerful tool to examine the mechanical damage and electrochemical degradation in lithium ion battery electrodes.